IMPLEMENTASI PROYEK PENGUATAN PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) MELALUI NILAI-NILAI TARIAN JARAN BODHAG DI SDN KANIGARAN 6 KOTA PROBOLINGGO - Nur Aulia Wijaya; Ludfi Arya Wardana; Faridahtul Jannah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study describes the Implementation of the Pancasila Student Profile Strengthening Project (P5) through the jaran bodhag dance at SDN Kanigaran 6 Probolinggo City. The focus of this study includes the implementation of activities, activity achievements, and supporting and inhibiting factors in the implementation of the P5 project. The background of the study is based on the importance of strengthening and preserving local culture through the Pancasila Student Profile Strengthening Project (P5) activities, in line with the demands of the Merdeka Curriculum which emphasizes the Pancasila dimension. The method used in this study is a qualitative method with a descriptive research type, which in this study describes how the process of implementing P5 activities starts from planning, implementation, to evaluation. Data collection techniques through observation, interviews and documentation. The results of this study indicate that the implementation of P5 through the values ​​of the jaran bodhag dance makes a significant contribution to the development of competencies, the formation of talents and potential of students in introducing local culture, expanding cultural history insights, and strengthening Pancasila values ​​according to the specified dimensions. The conclusion of this study is that the implementation of P5 activities through the values ​​of the Jaran Bodhag dance at SDN Kanigaran 6, Probolinggo City, has a positive impact on students, this is proven by the fact that this culture-based learning process can instill and develop students' character in accordance with the dimensions of the Pancasila student profile, and increase awareness of the importance of preserving cultural heritage as part of the nation's identity.